2012
DOI: 10.1002/dta.1394
|View full text |Cite
|
Sign up to set email alerts
|

UDP‐glucuronosyltransferase 2B17 genotyping in Japanese athletes and evaluation of the current sports drug testing for detecting testosterone misuse

Abstract: Ethnicity has been found to influence urinary testosterone glucuronide to epitestosterone glucuronide (T/E) ratios among athletes. Uridine diphospho-glucuronosyltransferase 2B17 (UGT2B17) is the most active enzyme in testosterone glucuronidation. UGT2B17 polymorphism analysis is rarely performed in Japanese athletes, and the influence of testosterone administration on steroid profiles and carbon isotope ratios, according to gene polymorphisms, in Asians remains unknown. The prevalence of UGT2B17 genotypes and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
42
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(52 citation statements)
references
References 25 publications
10
42
0
Order By: Relevance
“…A 29% increase in T/E ratio could be discerned first after the individuals homozygous for the deletion polymorphism in UGT2B17 were excluded. Furthermore, our results confirm a strong link between UGT2B17 deletion polymorphism and urinary testosterone levels in our female study group (9, 26). Here we show for the first time a link between a SNP in the promoter region of CYP17 and epitestosterone excretion in females.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…A 29% increase in T/E ratio could be discerned first after the individuals homozygous for the deletion polymorphism in UGT2B17 were excluded. Furthermore, our results confirm a strong link between UGT2B17 deletion polymorphism and urinary testosterone levels in our female study group (9, 26). Here we show for the first time a link between a SNP in the promoter region of CYP17 and epitestosterone excretion in females.…”
Section: Discussionsupporting
confidence: 87%
“…The ratio of A/Etio and 5α-diol/5β-diol does not seem to be affected during HC application, which is important for doping control purposes. However, the 5α-diol/5β-diol ratio, an important marker for dihydrotestosterone doping (40), is affected by the UGT2B17 deletion polymorphism (12, 26, 41) as 5β-diol is mainly glucuronidated by UGT2B17 (8). We and others have reported that A/E ratio is a sensitive marker for testosterone doping.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8] In these individuals, the glucuronidation of T is significantly decreased resulting in low natural T/E ratios that are only slightly elevated after illicit T administration. [11,14] Consequently, further information on the T metabolism in consideration of the different UGT2B17 genotypes has been desirable. [9][10][11] Neither the implementation of an expanded steroid profile taking sulphoconjugated (SULF) T and E into account nor a steroidomics approach could clearly show how administered T is preferentially excreted if not as T-GLUC.…”
Section: Introductionmentioning
confidence: 99%
“…Crystallised epitiostanol sulfoxide (1.7 mg, 24% yield) was obtained and identified by NMR spectroscopy with 1 H, 13 Differences in 13 C chemical shifts between epitiostanol and the corresponding sulfoxide ( ıC in ppm) were −4.80 (C-1), 16.06 (C-2), 15.45 (C-3), −5.04 (C-4) and 5.37 (C-5). These chemical shifts were consistent with the occurrence of a sulphur atom attached to the more electronegative oxygen atom.…”
Section: Synthesis Of Epitiostanol Sulfoxidementioning
confidence: 99%
“…Urine samples were prepared according to the common steroid analytical procedure validated for sports doping tests [16]. In brief, 3 mL of human urine fortified with 50 l of I.S.…”
Section: Sample Preparationmentioning
confidence: 99%